PENGARUH CARBON ACCOUNTING, BUSINESS STRATEGY, DAN SYSTEMATIC RISK TERHADAP ECONOMIC PERFORMANCE (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2013 – 2017) - Arry Eksandy; Retno Ayu Triani (Universitas Muhammadiyah Tangerang, 2019)
This study aims to determine the effect of carbon accounting, business strategy, and systematic risk on economic performance which are manufacture companies listed in Indonesia Stock Exchange in 2013-2017. Through of the research is quantitative.The population of this research is 13 manufacturing companies which are listed in Indonesia Stock Exchange in 2013-2017. The sample collection technique has been done by using purposive sampling method and 65 samples during 2013-2017 have been obtained. The data has been conducted by using secondary data which has been selected by using documentation techniques which consist of 2013-2017 manufacturing company annual report. The data analysis method of this research has been carried out by using panel regression analysis.The result of this research shows that carbon accounting and business strategy do not give any influence to the economic performance whereas the systematic risk gives influence to the economic performance.